1996
DOI: 10.1021/bi960684g
|View full text |Cite
|
Sign up to set email alerts
|

Interlobe Communication in 13C-Methionine-Labeled Human Transferrin

Abstract: [1H, 13C] NMR investigations of metal-induced conformational changes in the blood serum protein transferrin (80 kDa) are reported. These are thought to play an important role in the recognition of this protein by its cellular receptors. [1H, 13C] NMR resonance assignments are presented for all nine methionine 13CH3 groups of recombinant deglycosylated human transferrin on the basis of studies of recombinant N-lobe (40 kDa, five Met residues), NOESY-relayed [1H, 13C] HMQC spectra, and structural considerations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…In recent studies, microcalorimetry of hTF, for example, shows that iron binds preferentially to the C-lobe which raises the T m of the N-lobe 4 mC. Lobe-lobe interaction has been shown in NMR experiments of hTF in which the methionine residues were labelled with "$C [31]. Titration calorimetry has been used to measure the interaction between the isolated N-and C-lobes of hTF [17] and of oTF [32], produced by recombinant techniques and\or by proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, microcalorimetry of hTF, for example, shows that iron binds preferentially to the C-lobe which raises the T m of the N-lobe 4 mC. Lobe-lobe interaction has been shown in NMR experiments of hTF in which the methionine residues were labelled with "$C [31]. Titration calorimetry has been used to measure the interaction between the isolated N-and C-lobes of hTF [17] and of oTF [32], produced by recombinant techniques and\or by proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between Lobes-A cooperative effect of one lobe on the other lobe has been convincingly documented in a number of studies using a variety of techniques, which include NMR of hTF (58), absorption spectra of oTF (59), pH-dependent iron release of LTF (60), calorimetric studies of both hTF and oTF (61-63), electrospray ionization mass spectrometry studies of hTF (43), iron release from monoferric LTF (64), analysis by urea gels (22), and chemical relaxation studies (65)(66)(67). Significantly, a number of these studies specifically attribute cooperative effects between the two lobes of hTF to participation of helix 12 from the C-lobe (2,68).…”
Section: Triad-lysmentioning
confidence: 98%
“…This fritless 100 mm capillary was packed with 12 cm of Eclipse XDB C 18 and a column flow rate of 0.12 mL min À1 and spray voltage of 1.8 kV were used. Only buffer solutions A and B were required for the reversed-phase chromatographic separation.…”
Section: Esi-ms-ms: Esi-ms and Ms-ms Data For The Model Peptide G-a-lmentioning
confidence: 99%
“…The same group has also reported an NMR spectroscopic study of cisplatin binding to human Trfe, [17] in which they observed that only the 13 C resonances that were previously assigned [18] to the d-CH 3 groups of M256 and M499 were influenced by adduct formation. In contrast, the T457 was established as a specific cisplatin binding site by Dyson et al [19,20] Cisplatin binding sites in human serum proteins have been characterised by using combined multidimensional liquid chromatography and ESI tandem mass spectrometry (MudPIT).…”
Section: Introductionmentioning
confidence: 96%